Psoriatic Nephropathy and its Correlation with hs-CRP: A Case Control Study - Kaur, Ishmeet (Indian Dermatol Online J, 2020)
BACKGROUND: Psoriasis is a multisystem disorder associated with various systemic diseases such as cardiovascular diseases, diabetes mellitus and metabolic syndrome. Renal involvement in patients with psoriasis is sparsely studied and its association is still unclear. AIM: The aim of this article was to study causal attributable renal involvement in patients with psoriasis and factors affecting the same. METHODS: Fifty patients with documented psoriasis were recruited after excluding any secondary causes of renal disease. They were subjected to routine investigations along with hs-CRP and specific investigations for kidney function including urine albumin creatinine ratio (ACR) and estimated glomerular filtration rate (eGFR). The eGFR and ACR of the patients were compared with 50 age- and sex-matched controls. Association with any disease-related factors such as severity and duration were assessed. Renal biopsy was planned in patient with ACR >500 mg/g creatinine. RESULTS: The mean eGFR (IQR) (ml/min/1.73 m(2)) of the case group was found to be 80.00 (71.00–95.75) and in the control group was 88.00 (75.25–99.00). This difference was not significant (P = 0.206). However, in the age group of > 30 years, the eGFR of disease group (78.50 ± 17.94) was significantly lower than that in the control group (88.96 ± 17.01, P = 0.023).The mean urine ACR (mg/g) in the disease group was found to be 13.359 ± 26.01 while that in the control group was found to be 5.66 (3.40–8.08), and the difference was not found to be clinically significant. Four patients with psoriasis had microalbuminuria as opposed to none of the controls. CONCLUSION: Subclinical albuminuria was found in 8 per cent of patients with psoriasis. Glomerular dysfunction with statistically significant reduction in eGFR was seen in psoriasis in age group of more than 30 years and those who had a long-standing disease. The renal involvement had positive correlation with hs-CRP indicating the role of inflammatory milieu. Further large-scale cohort studies would help assess this aspect in further details. LIMITATION OF THE STUDY: Sample size was small. Large-scale studies would be required to further substantiate these observations.